Glucose Oxidase/Nano-ZnO/Thin Film Deposit FTO as an Innovative Clinical Transducer: A Sensitive Glucose Biosensor - Naderi Asrami, Padideh; Aberoomand Azar, Parviz; Saber Tehrani, Mohammad; Mozaffari, Sayed Ahmad (Frontiers in Chemistry, 2020)
In the present research, a new biocompatible electrode was proposed by a rapid and direct glucose biosensing technique. Nanostructured zinc oxide (Nano-ZnO) was sputtered by reactive direct current (DC) magnetron sputtering system on a pre-covered fluorinated-tin oxide (FTO) conductive layer. Spin-coated polyvinyl alcohol (PVA) at optimized instrumental deposition conditions were applied to prepare the effective medium for glucose oxidase (GOx) enzyme covalent immobilization through cyanuric chloride (GOx/Nano-ZnO/PVA/FTO). Surface design for glucose biosensing was set up, in which PVA acted as an electrostatic repulsive layer for the anionic interferents at biological pH. The electrochemical behavior of glucose on the fabricated GOx/Nano-ZnO/PVA/FTO biosensor was investigated by I-V techniques. In addition, field emission-scanning electron microscopy (FE-SEM) and electrochemical impedance spectroscopy (EIS) were applied to assess the morphology of the modified electrode surface. The I-V results indicated good sensitivity for glucose detection (0.041 mA per mM) within 0.2 – 20 mM and the limit of detection was as 2.0 M. We believe that such bio-devices have good potential for tracing a number of bio-compounds in biological fluids along with excellent accuracy, selectivity, and precise analysis. The fast response of fabricated GOx/Nano-ZnO/PVA/FTO biosensor (less than 3 s) could allow most types of real-time analysis.